Utilisation of terrestrial habitat by Black Brant Branta bernicla nigricans after the Great East Japan Earthquake of 2011 - Shimada, Tetsuo; Yamada, Yumi; Hijikata, Nayoa; Tokita, Ken-Ich; Uchida, Kiyoshi; Kurechi, Masayuki; Suginome, Hitoshi; Suzuki, Yasushi; Higuchi, Hiroyoshi (Wildfowl, 2018)
On 11 March 2011, the Great East Japan Earthquake hit eastern Japan, causing an enormous tsunami that swept through a wide area of the Pacific coast of Japan. Black Brant Branta bernicla nigricans, which forage on sea grass and marine algae in the shallow coastal waters, were one of the many bird species affected by this event. Here we overlay satellite-tracking data upon GIS landform and land-use layers to assess the consequences of the tsunami on habitat utilisation by the geese. Satellite-tracking of Black Brant following the tsunami showed that along the southern Sanriku coast in northern Honshu, where habitat had been affected by the tsunami, the geese exploited not only their traditional coastal areas but also terrestrial sites including paddy fields. Overall, 37 (4.3%) of the 868 satellite locations were confirmed to be in terrestrial habitats, possibly resulting from habitat loss in intertidal areas following the tsunami. Field observations also found geese feeding in flooded paddy fields 2 km inland of the coast. These results illustrate an adaptive behaviour by the geese to large-scale environmental changes.